Trend Of Entrepreneurship Education And Entrepreneurial Practices On Entrepreneurial Interest In Higher Education - Alifia, Atika; Tyas, Widantining; tholibi, I'anatut; Wulandari, Siti Sri (Jurnal Pendidikan Edutama, 2024)
Carrying out a literature review regarding the influence of entrepreneurial education and entrepreneurial practices on entrepreneurial interest is the aim of this study with Systematic Literature Review (SLR) being the research method. Documentation of all articles with research related to this study report was carried out to collect data. A total of 40 articles sourced from Sinta, Google Scholar and international journals indexed by Scopus were used in this study. From this study, it was found that interest in entrepreneurship is significantly influenced by entrepreneurship education. And entrepreneurial practice. The results of the literature review also found that entrepreneurship education and entrepreneurial practices can be applied as a strategy in increasing individual entrepreneurial interest in higher education. Therefore, it is important for educational institutions and the government to improve entrepreneurship education, develop mentorship programs, and create better entrepreneurial opportunities to facilitate the development of students' entrepreneurial interests.